VB.NET Developer's Guide - Wakefield, Cameron (Syngress Publishing, Inc., 2011)
Visual Basic has long been the language of choice when designing Windows-based applications and the Web. Touted as both the most popular and productive computing language, Visual Basic has amassed quite a following of devoted programmers, and is a sought after programming skill. With the introduction of.NET Enterprise, Microsoft launch VB.NET, offering a streamlined, simplified version of Visual Basic language. With increased power, scalability, functionality and reliability, VB.NET is positioned to be the most productive tool in a programmer's toolbox. VB.NET Developer's Guide is written for previous Visual Basic Programmers looking to harness the power of the new features and functionality incorporated in Visual Basic.NET. - Timely coverage of newly released product which Visual Basic users will be eager to learn - VB.NET Developer's Guide is one of the first comprehensive reference for programmers and developers anxious to learn about the new technology - You can take it with you. The book comes with Syngress' revolutionary Wallet CD containing a printable HTML version of the book, all of the source code examples and demos of popular VB to VB.NET upgrade and programming tools